Treatment in congenital pulmonary airway malformation: A case report and review of the literature [Kongenital pulmoner havayolu malformasyonunda tedavi: Olgu sunumu ve literatür derlemesi] - (:unkn) unknown (My University, 2013)
Congenital pulmonary airway malformation (CPAM) is a rare developmental abnormality of the lung that has been associated with the presence of rhabdomyosarcoma, pleuropulmonary blastoma, and most commonly bronchioalveolar carcinoma of the lung. Here, we report the case of a 10-year-old boy complaining of only chest pain. Some authors advocate simple observation because of the lack of data on the incidence of long-term complications. However, there are very few described cases where CPAM have remained asymptomatic throughout life; complications eventually develop in virtually all patients. Most authors advocate elective resection of all CPAM because of the risk of complications, such as infection, hemorrhage, pneumothorax, and malignant transformation. Since resection will be required sooner or later for CPAM, it is best not to wait for complications to occur. In our opinion surgery can be delayed until the child is approximately 9 months old to allow for possible resolution without taking the risk of malignancy.
Keywords: Chest pain; Congenital; Lung; Malformation; Neoplasm; Therapy